Tetranuclear copper(II) complexes with macrocyclic and open-chain disiloxane ligands as catalyst precursors for hydrocarboxylation and oxidation of alkanes and 1-phenylethanol - Zaltariov, Mirela-Fernanda (2015)
Two new tetranuclear complexes [Cu-4(mu-O)(L-1)-Cl-4] and [Cu-4(mu(4)-O)(L-2)(2)Cl-4] (2), where H2L1 is a macrocyclic ligand resulting from [2+2] condensation of 2,6-diformy1-4-methylphanol (DFF) and 1,3-bis(aminopropy1)tetramethyldisiloxane, and HL2 is a 1:2 condensation product: of DFF with trimethylsilyl p-aminobenzoate, have been prepared. The structures of the products were established by Xray diffraction. The complexes have been characterised by FTIR, UV/Vis spectroscopy, ES1 mass-spectrometry and magnetic susceptibility measurements. The latter revealed that the letrftriuclear complexes can be descr bed as two ferromagnetically coupled dinuclear units, in which the two copper(II) ions interact antiferromacinetically. The ccimpi.iunds act as homogeneous catalyst precursors for a number of single-pot reactions, including (I) hydrocarbaxylation, with CO, H2O and K2S2O8, of a variety of linear and cyclic (n = 5-8) alkanes into the corresponding Cn+1 carboxylic acids, (ii) peroxidative oxidation of cyclohexane, and (iii) solvent-free microwave-assisted oxidation of 1-phenyletha.nol.